Prioritizing Success Factors for Start-ups in Indonesia Using the Best Worst Method (BWM): A Decision-Making Approach - Safitri, Yulita Dwi; Pebriana, Rina; Suasri, Eni (Frontier Management Science, 2024)
The rapid growth of Indonesia’s start-up ecosystem presents both opportunities and challenges for new ventures striving for sustainability and competitiveness. This study applies the Best Worst Method (BWM) to prioritize key success factors for start-ups in Indonesia, providing a structured framework for decision-making. Six critical factors were evaluated: access to funding, innovation capability, market competition, regulatory environment, talent acquisition, and scalability potential. Through pairwise comparisons, this research identifies access to funding as the most critical factor, while scalability potential is considered the least influential in determining start-up success. The findings offer valuable insights for entrepreneurs, investors, and policy-makers, highlighting areas where targeted support can enhance the growth and sustainability of start-ups. This study contributes to the ongoing discourse on start-up development in emerging economies by providing a decision-making tool to guide strategic priorities within Indonesia’s dynamic entrepreneurial landscape.